Mepolizumab’s (Anti-Interleukin-5) Role in Severe Asthma: A Literature Review - Atikanur, Atikanur; Wijaya, Dewi; Esha, Indi; Simanjuntak, Arya Marganda (Jurnal Respirologi Indonesia, 2024)
One type of asthma that is difficult to treat is severe asthma, which is asthma that is uncontrolled even when the patient is taking medication or trigger factors. It can be treated with the finest therapy but will worsen if high-dose treatment is discontinued. Age, gender, obesity, hypersensitivity, and immunological factors are all directly related to the onset of asthma. A complicated illness, severe asthma has many clinical symptoms and treatment choices. Chronic airway inflammation and lung tissue remodeling are its defining features. This literature review aims to describe how mepolizumab works in patients with severe asthma. Mepolizumab mainly inhibits the IL-5 cytokine from binding to IL-5 receptor subunits through the nanomolar potential, which inhibits IL-5 from binding to receptors on the surface of eosinophils. In contrast to the placebo group, patients on mepolizumab had an average 50% decrease from the baseline Prednisone dosage. With Mepolizumab, the yearly exacerbation rate was 1.44 RR, while it was 2.12 RR with placebo. The injection of monoclonal antibodies, such as mepolizumab, as a form of therapy in addition to treating severe eosinophilic asthma is advised by the GINA guideline for 2022. Mepolizumab's mode of action blocks IL-5 from binding to receptors on eosinophil surfaces, which lowers eosinophil recruitment, activation, production, growth, and survival, as well as eosinophil-mediated inflammation.